Incidence of Osteoporosis-Related Complications Following Posterior Lumbar Fusion. Issue 6 (September 2018) - Bjerke, Benjamin T.; Zarrabian, Mohammad; Aleem, Ilyas S.; Fogelson, Jeremy L.; Currier, Bradford L.; Freedman, Brett A.; Bydon, Mohamad; Nassr, Ahmad
Study Design: Retrospective review. Objectives: This study investigates the prevalence of adverse postsurgical events, or osteoporosis-related complications (ORCs), following spinal fusion. Methods: Patients undergoing primary posterior thoracolumbar or lumbar fusion by 1 of 2 surgeons practicing at a single institution were analyzed from 2007 to 2014. ORCs were defined in one of the following categories: revision surgery, compression fracture, proximal junctional kyphosis, pseudarthrosis, or failure of instrumentation. Patients with a bone mineral density of the hips and/or spine performed within 1 year of the index procedure were included. Patients were stratified into normal bone density, osteopenia, and osteoporosis using WHO guidelines. Patients were excluded if they were younger than 18 years at the time of surgery, with infection, malignancy, skeletal dysplasia, neuromuscular disorders, concomitant or staged anterior-posterior procedure, or fusion performed because of trauma. Results: Out of 140 patients included, the prevalence of normal bone density was 31.4% (44/140), osteopenia 58.6% (82/140), and osteoporosis 10.0% (14/140). There were no differences between groups for gender, age, body mass index, and interbody device rate. The overall prevalence of ORCs was 32.1% (45/140). By group, there was a prevalence of 22.7% (10/44), 32.9% (27/82), and 50.0% (7/14) for normal bone density, osteopenia, and osteoporosis, respectively. These differences were significantly higher for both the osteopenia and osteoporosis groups. Conclusions: Patients with T scores below −1.0 undergoing posterior lumbar fusion have an increased prevalence of ORCs. Consideration of bone density plays a crucial role in patient selection, medical management, and counseling patient expectations.